2016
DOI: 10.4067/s0718-381x2016000100018
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Odontogenic Tumors: Analysis of 156 Cases in a Brazilian Population

Abstract: ABSTRACT:The objective of this study was to determine the distribution of epithelial odontogenic tumors diagnosed histologically in a period of 41 years in a Brazilian population according to age, gender, site affected and compare these data with previously reported studies from other countries. Data of epithelial odontogenic tumors diagnosed were collected from the files of the Oral Pathology Laboratory of Federal University of Rio Grande do Norte, Natal, RN, Brazil, and entered in a standardized form for lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Odontogenic tumors originate from the tissues of teeth forming apparatus due to the different degrees of inter-tissue interactions and the various growth patterns. [22] Clinically and radio-graphically; both AB and AC are highly similar. However, AC can be expected if there are uncommon features of AB such as: rapid onset of swelling, pain, paresthesia and perforation of the cortical plate.…”
Section: Discussionmentioning
confidence: 96%
“…Odontogenic tumors originate from the tissues of teeth forming apparatus due to the different degrees of inter-tissue interactions and the various growth patterns. [22] Clinically and radio-graphically; both AB and AC are highly similar. However, AC can be expected if there are uncommon features of AB such as: rapid onset of swelling, pain, paresthesia and perforation of the cortical plate.…”
Section: Discussionmentioning
confidence: 96%
“…Controversy regarding which gender predominates in ameloblastoma exists. Cavalcante et al 2016 reported slight female preference [22]. Ramos et al [12] stated that ameloblastoma exhibits no gender predilection.…”
Section: Ghazi Ommentioning
confidence: 99%
“…Os cistos odontogênicos constituem um grupo de diversas lesões heterógenas com características histopatológicas e manifestações clínicas diversas (Cavalcante et al, 2016). De acordo com a Organização Mundial da Saúde (2005),o Cisto Periapical CP de origem inflamatória é o mais comum, sendo conhecido também como cisto radicular.…”
Section: Introductionunclassified